2011
DOI: 10.1099/mic.0.045146-0
|View full text |Cite
|
Sign up to set email alerts
|

A simple plasmid-based system that allows rapid generation of tightly controlled gene expression in Staphylococcus aureus

Abstract: We have established a plasmid-based system that enables tightly controlled gene expression and the generation of GFP fusion proteins in Staphylococcus aureus simply and rapidly. This system takes advantage of an Escherichia coli-S. aureus shuttle vector that contains the replication region of the S. aureus theta-mode multiresistance plasmid pSK41, and is therefore a stable lowcopy-number plasmid in the latter organism. This vector also contains a multiple cloning site downstream of the IPTG-inducible Pspac pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…We found that compound 1 inhibited the growth of permeable E. coli with an MIC 50 of 27±9 µM, while compound 2 was also inhibitory with an MIC 50 of 84 µM. 27 The inhibition curve for 2 against envA1 E. coli was unusually steep. Although this type of curve can indicate aggregation of a small molecule inhibitor, we note that none of the in vitro inhibition curves for 2 toward FtsZ show this behavior.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…We found that compound 1 inhibited the growth of permeable E. coli with an MIC 50 of 27±9 µM, while compound 2 was also inhibitory with an MIC 50 of 84 µM. 27 The inhibition curve for 2 against envA1 E. coli was unusually steep. Although this type of curve can indicate aggregation of a small molecule inhibitor, we note that none of the in vitro inhibition curves for 2 toward FtsZ show this behavior.…”
Section: Resultsmentioning
confidence: 76%
“…20 Liew et al described a S. aureus system for visualization of fluorescent Z-rings, but that system requires tight control of the expression of more than one plasmid making it more complex for screening purposes than an E. coli -based system. 27 Experiments were conducted to determine times of induction that would allow for expression of FtsZ-YFP and co-localization of fluorescent and wild-type FtsZ at mid-cell during division (detailed in Methods). Fluorescence micrographs showed that prior to arabinose induction there was no observable background fluorescence (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…A more direct approach to demonstrate gene essentiality is to place the gene of interest under the control of an inducible promoter in the chromosome or in a low-copy plasmid and assess the essentiality based on survival in the presence or absence of the inducer (Fan et al , 2001; Jana et al , 2000; Liew et al , 2011; Zheng et al , 2005). The IPTG-inducible P spac promoter has been favoured in these systems.…”
Section: Gene Essentiality Testingmentioning
confidence: 99%
“…Gene deletions were made using the pMAD and pKFC allelic replacement systems (42,43). Complementation was performed using pLOW (44), and double mutants were created through ϕ85 transduction of a marked deletion into unmarked deletion backgrounds.…”
Section: Methodsmentioning
confidence: 99%